1964
DOI: 10.1111/j.1151-2916.1964.tb14368.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity of Cubic Solid Solutions in the System CaO—Y2O3—ZrO2

Abstract: 0 1 2 3 4 5 DISTANCE FROM HOT FACE (IN.) Fig. 18. Distribution of lime plus silica after slogging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(110 citation statements)
references
References 11 publications
12
98
0
Order By: Relevance
“…The first trivalent Al 3+ ion conductor reported by us was in the above introduced Al 2 (WO 4 ) 3 system, with an electrical conductivity of 3.2 × 10 −6 S·cm −1 at 600°C [5]. This remains considerably below > 10 −4 S·cm −1 , a value more in line with values exhibited by commercialized solid electrolytes such as yttria stabilized (YSZ) and calcia stabilized zirconia (CSZ) [12].For the purpose of realizing a practical Al 3+ ion conducting solid electrolyte, NASICON (denotes Na + Super Ion CONductor) [13], composed of a three dimensional network structure that is more suitable as compared with a two-dimensional layered structure, was chosen in our study given its rather open crystallographic structure. This is J Electroceram (2010) 24:331-344…”
supporting
confidence: 70%
“…The first trivalent Al 3+ ion conductor reported by us was in the above introduced Al 2 (WO 4 ) 3 system, with an electrical conductivity of 3.2 × 10 −6 S·cm −1 at 600°C [5]. This remains considerably below > 10 −4 S·cm −1 , a value more in line with values exhibited by commercialized solid electrolytes such as yttria stabilized (YSZ) and calcia stabilized zirconia (CSZ) [12].For the purpose of realizing a practical Al 3+ ion conducting solid electrolyte, NASICON (denotes Na + Super Ion CONductor) [13], composed of a three dimensional network structure that is more suitable as compared with a two-dimensional layered structure, was chosen in our study given its rather open crystallographic structure. This is J Electroceram (2010) 24:331-344…”
supporting
confidence: 70%
“…3. This hole has a simple Lorentzian shape without any anti-holes and side- by several authors [25,26,27] are also shown.…”
Section: Fi"-aluminamentioning
confidence: 92%
“…The temperature dependence of the trivalent A13+ ion conductivity of (AlxZrl_x)a/(4_x)Nb(PO4) 3 is presented in Fig. 3 with the data of the trivalent Sc 3+ ion conducting solids reported to show the optimum ion conductivity among the 8c2(WO4) 3 type and the M1/zZr2(PO4)3 type series, and the data of representative commercially available oxide anion conductors of YSZ [13] and CSZ [13]. As can be easily recognized, the (AlxZrt_x)4/(4_~)Nb(PO4) 3 solid electrolyte possesses the highest trivalent ion conductivity among the conductors, and the AI 3 § ion conducting solid electrolyte was combined with YSZ whose ion conductivity is similar to that of (A1,Zr,x)4xa.,Nb(PO4)~ at the operating temperature of 450 ~ and a new type of NO gas sensor was fabricated as introduced in Fig.…”
Section: Experimental Descriptionmentioning
confidence: 98%